Beach practices. Models for design-driven seaside regenerations - Vincenzo Cristallo; Ivo Caruso (Agathón)
Regeneration as a design practice and as a collective goal has many ways of manifesting itself. In addition to being normally associated with the principles of sustainability, and to include actions aimed at the recovery, reuse and enhancement of goods and services, over time it has achieved a ‘multifaceted’ meaning capable of including models and examples with original and exploratory characteristics. Among these is the seaside environment, and the beach in particular, examined in this essay on the basis of the results of two research projects with field and desk contents, which recognize that seashores are an integral part of the very metaphor of inhabited space. Therefore, net of a corollary of specific functions, from this area the complexity of contemporary living is also manifested in the mutability of the ‘regenerative genres’, genres that in the paper are shown – and this is its declared argumentative objective – in the scientific perimeter of a ‘design for territories’ socially declined in connective and relational values.